The Impact of Energy Consumption and Economic Growth on the Saudi Arabia’s Carbon Emissions - Khan, Uzma; Khan, Aarif Mohammad (International Journal of Energy Economics and Policy, 2024)
This study is an initial attempt to examine the correlation between energy consumption and economic growth in Saudi Arabia's carbon emissions from 1985 to 2021. Notably, despite the prominence of low-carbon economic growth in the Paris Agreement and the Sustainable Development Goals, this specific link has yet to be previously investigated. The study used an autoregressive distributed lag (ARDL) approach to analyse the relationship between carbon emissions from energy consumption and economic development in Saudi Arabia. The bound test shows that the relationship has been going on for a long time, and the error correction equation shows that the endogenous and exogenous variables are negatively related by 0.58. This indicates that the system adjusts its previous period's imbalance by 58% within a single period. The Granger causality test reveals a one-way causal relationship between energy use and carbon dioxide emissions, economic growth, and oil consumption. Additionally, the generation of energy through oil-based power plants is known to result in the release of carbon emissions, although in a unidirectional manner. It is necessary to prioritize exploring alternate methods for power generation, particularly those that rely on non-conventional or renewable energy sources.